Efficient Isolation and Enrichment of Mesenchymal Stem Cells from Human Embryonic Stem Cells by Utilizing the Interaction between Integrin α5β1 and Fibronectin - Byung‐Hyun Cha; Jin‐Su Kim; Alvin Bello; Geun‐Hui Lee; Do‐Hyun Kim; Byoung Ju Kim; Yoshie Arai; Bogyu Choi; Hansoo Park; Soo‐Hong Lee (Advanced Science, 2020)
Abstract Human pluripotent stem cells (hPSCs) are a potent source of clinically relevant mesenchymal stem cells (MSCs) that confer functional and structural benefits in cell therapy and tissue regeneration. Obtaining sufficient numbers of MSCs in a short period of time and enhancing the differentiation potential of MSCs can be offered the potential to improve the regenerative activity of MSCs therapy. In addition, the underlying processes in the isolation and derivation of MSCs from hPSCs are still poorly understood and controlled. To overcome these clinical needs, an efficient and simplified technique on the isolation of MSCs from spontaneously differentiated human embryonic stem cells (hESCs) via integrin α5β1 (fibronectin (FN) receptor)‐to‐FN interactions (hESC‐FN‐MSCs) is successfully developed. It is demonstrated that hESC‐FN‐MSCs exhibit a typical MSC surface phenotype, cellular morphology, with the whole transcriptome similar to conventional adult MSCs; but show higher proliferative capacity, more efficient trilineage differentiation, enhanced cytokine secretion, and attenuated cellular senescence. In addition, the therapeutic potential and regenerative capacity of the isolated hESC‐FN‐MSCs are confirmed by in vitro and in vivo multilineage differentiation. This novel method will be useful in the generation of abundant amounts of clinically relevant MSCs for stem cell therapeutics and regenerative medicine.